(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Effective tracking and timely assessment of surgical wounds are crucial for minimizing post-operative complications such as infections and delayed healing. This article explores the use of Google Forms as a No-cost, efficient tool for monitoring surgical site Infection and promoting patient self-reporting for post-operative care. We discuss the development of a "Surgical Site Infection Tracker" form, which enables healthcare providers to track the healing progress of surgical wounds remotely. The form includes various assessment parameters such as pain, redness, drainage, and signs of infection, and allows for easy integration with Google Sheets for data analysis. The potential benefits, limitations, and ethical considerations of this method are also explored.